Internationalization and Decolonization in UK Higher Education: Are We There Yet? - Fakunle, Omolabake; Kalinga, Chisomo; Lewis, Vicky (International Higher Education, 2022)
Different interpretations and contestations related to internationalization and decolonization in universities result in a contradictory picture. Even where Western institutions ostensibly embrace the drive for decolonization, their Anglocentric, colonial interpretations of internationalization are often at odds with this effort—in the areas of strategy and policy, as well as teaching practice and research. Changes in approach are needed in order for these two processes to work hand-in-hand within a complex conceptual and operating context.